2020
DOI: 10.1098/rsos.200664
|View full text |Cite
|
Sign up to set email alerts
|

Are post-error adjustments influenced by beliefs in free will? A failure to replicate Rigoni, Wilquin, Brass and Burle, 2013

Abstract: In this pre-registered study, we tried to replicate the study by Rigoni et al. 2013 Cognition 127 , 264–269. In the original study, the authors manipulated the participants’ belief in free will in a between-subject design and subsequently measured post-error slowing (i.e. slower responses after an incorrect trial compared with a correct trial) as a marker of cognitive control. They found less post-error slowing in the group with reduced belief in free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…Despite the mounting evidence that manipulating belief in free will influences behavior, a number of studies have reported difficulties in replicating some key results (Crone & Levy, 2019;Eben et al, 2020;Genschow, Hawickhorst, et al, 2020;Giner-Sorolla et al, 2016;Monroe et al, 2017;Nadelhoffer et al, 2020;Open Science Collaboration, 2015;Schooler et al, 2014;Shariff & Vohs, 2014;Zwaan, 2014). For example, Monroe et al (2017) found no effect of diminishing participants' belief in free will on moral behavior, judgments of blame, or punishment decisions.…”
Section: Failed Replicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the mounting evidence that manipulating belief in free will influences behavior, a number of studies have reported difficulties in replicating some key results (Crone & Levy, 2019;Eben et al, 2020;Genschow, Hawickhorst, et al, 2020;Giner-Sorolla et al, 2016;Monroe et al, 2017;Nadelhoffer et al, 2020;Open Science Collaboration, 2015;Schooler et al, 2014;Shariff & Vohs, 2014;Zwaan, 2014). For example, Monroe et al (2017) found no effect of diminishing participants' belief in free will on moral behavior, judgments of blame, or punishment decisions.…”
Section: Failed Replicationsmentioning
confidence: 99%
“…For example, we did not have enough data to investigate the influences of free will belief manipulations on neurocognitive processes (Rigoni et al, 2012;Rigoni et al, 2011;Rigoni et al, 2015), feelings of alienation (Seto & Hicks, 2016), attributions of other people's actions (Genschow et al, 2017a), perceived meaningfulness of life (Crescioni et al, 2016;, perceived gratitude (MacKenzie et al, 2014), counterfactual thinking (Alquist et al, 2015, or risk taking behavior (Schrag et al, 2016). For these and potential other variables that have not been studied yet, it remains open to what degree they are influenced by free will belief manipulations, although one of the effects on neurocognitive processes recently failed to replicate (Eben et al, 2020).…”
Section: Little Evidence For Downstream Consequences and Its Potential Reasonsmentioning
confidence: 99%
“…In a broader perspective, our findings have implications for the attribution of moral responsibility. Rigoni and colleagues (Rigoni et al, 2012(Rigoni et al, , 2013(Rigoni et al, , 2015 observed that weakening belief in intentional control reduces behavioural and neural markers of performance monitoring and decreases the feeling of having deliberate control over a motor action (but see Eben et al, 2020). In other words, they showed that the basic neurocognitive processes that underlie voluntary behaviour are influenced by the extent to which people believe they can exert intentional control.…”
Section: Discussionmentioning
confidence: 99%
“…Because slowing down after an error is sometimes associated with an increase in accuracy, PES is traditionally attributed to adaptive adjustments of decision policies, favoring a more cautious response style to improve performance in the subsequent trial (Rabbitt and Vyas 1970, Smith and Brewer 1995, Cavanagh et al 2014, Siegert et al 2014, Purcell and Kiani 2016, Steinhauser and Andersen 2019, Beatty et al 2020). However, several recent studies have revealed that PES can also occur in a somewhat ‘maladaptive’ way as slowing does not necessarily lead to improvement in accuracy; in fact, PES can even come with a decrease in decision accuracy (Ceccarini et al 2019, Eben et al 2020b, Kirschner et al 2020, Schroder et al 2020, Smith et al 2020, Compton et al 2021). These findings indicate that the functional significance of PES may vary according to the context in which it is observed.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, studies reporting a maladaptive PES rather use reaction time tasks that are quite simple such that the overall level of choice accuracy is usually much higher (i.e. more between 80 – 100% of correct choices) (Notebaert et al 2009, Nunez Castellar et al 2010, Houtman et al 2012, Eben et al 2020b, Kirschner et al 2020, Li et al 2020, Compton et al 2021). In such settings, errors represent infrequent and unexpected events that may catch attention, resulting in a maladaptive PES that deteriorates (rather than enhances) choice accuracy in the consecutive trial (Sokolov 1963, Nunez Castellar et al 2010, Houtman et al 2012).…”
Section: Introductionmentioning
confidence: 99%